Enhancing the Geotechnical Behavior of Expansive Soil-Coconut Fiber Mixtures with Various Agricultural Ash Waste: A Comparative Study - Anita Widianti; Muhammad Hatta; Anita Rahmawati; Dian Eksana Wibowo (Environment and Natural Resources Journal)
Expansive soil is classified as problematic because it has a high plasticity index, high swelling shrinkage due to water content fluctuations, and low bearing capacity. This research focused on stabilizing it with coconut fiber and three different types of agricultural ash: sugarcane bagasse ash (SBA), rice husk ash (RHA), and coir-wood ash (CWA). Coconut fiber made up 0.75% of the material and acted as reinforcement. The three types of ash were used in varying proportions (0%, 2%, 4%, 6%, 8%, and 10% of the mixture’s total weight) to reduce swelling shrinkage and enhance bearing capacity through cementation. The mixture was compacted to the soil’s Maximum Dry Density and Optimum Moisture Content. Then, the specimens were cured for different durations. The California Bearing Ratio (CBR) testing specimens were cured for 7 days and 14 days, while those for Unconfined Compressive Strength (UCS) testing were cured for 14 days and 28 days. All testing complied with ASTM standards. The results showed that strengthening coconut fiber and stabilizing with three different types of ash in expansive soil increased CBR and UCS values and significantly reduced swelling. These improvements were directly proportional to increases in the ash content and curing time. Optimal outcomes were achieved with all three types of ash at a similar content level, ranging from 8% to 10%. For specimens cured for 14 days, CBR values increased to 9.24% (RHA), 11.96% (SBA), and 13.44% (CWA), representing an improvement of 6.4 to 9.8 times compared to unstabilized soil. For specimens cured for 28 days, UCS values increased to 440.69 kPa (CWA), 472.45 kPa (SBA), and 482.96 kPa (RHA), representing an improvement of 9.6 to 10.6 times compared to unstabilized soil. A swelling value of 0% was achieved in the soil-coconut fiber mixture stabilized with a 10% concentration of RHA/SBA/CWA. These findings suggest that each type of ash has advantages and disadvantages, but all ultimately contribute to increasing soil strength and eliminating swelling. By utilizing agricultural waste for expansive soil stabilization, significant benefits can be achieved for the government, industry, and local communities. Developing technical guidelines for using agricultural waste as a soil stabilizer will greatly facilitate its practical application in the field.